Characterization of total DNA demethylation potential and its PBDE components of household airborne dust in three Chinese cities - Xiaotong Zhang; Wenying Zhang; Fengjing Song; Tingting Liu; Chengyu Chen; Xiaomin Xie; Chao Wang; Hang Du; Lin Fan; Weiyi Zhang; Yiming Sun; Xianliang Wang (Environment International)
Household dust is a major reservoir for indoor pollutants, yet its epigenetic effects remain poorly characterized. This study investigated household airborne dust’s total DNA demethylation potential (TDP) and its association with 14 priority polybrominated diphenyl ethers (PBDEs) in 43 residences across Lanzhou, Suzhou, and Harbin. The median TDP (5-AZA-CdR equivalent) was 0.016 (range: 0–1.006), while the median Σ14PBDEs concentration was 2085.73 ng/g (range: 64.51–26,746.47 ng/g), with BDE-209 dominating (>90 %). Exploratory factor analysis identified three principal components explaining 80.59 % of the variance, with PBDE levels significantly influenced by socioeconomic status, building materials, household products, and occupant behaviors (P < 0.05). Linear regression models revealed significant negative associations between TDP and BDE-153 (β = -0.020; 95 % CI: −0.035 to −0.005, β = -0.003; 95 % CI = −0.045 to −0.016), BDE-183 (β = -0.003; 95 % CI: −0.006 to −0.001), BDE-209 (β = -0.000; 95 % CI: −0.000 to −0.000), and Factor 2-derived congeners (β = -0.389; 95 % CI = -0.626 to −0.152, β = -0.389; 95 % CI = −0.616 to −0.162). In contrast, BDE-66 exhibited a positive association (β = 0.052; 95 % CI: 0.022 to 0.082). The findings suggest that household dust and its PBDE components may pose epigenetic health risks through DNA demethylation alterations.